Accelerate urban sustainability through European action, optimization models and decision support tools for energy planning - Federica Gaglione; David Ania Ayiine Etigo (TeMA: Journal of Land Use, Mobility and Environment, 2022)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility, and environment, thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation. Section aims at presenting the latest updates in the territorial and urban legislative sphere. The theme of energy and its related energy consumption is a leading theme in the European scientific debate for the continuous pursuit of urban development. In this direction, the contribution of this review notes illustrates on the one hand optimization models and decision support tools produced so far to improve the energy organization at different urban scales and on the other highlights within the cards, strategies and actions carried out forward from the European Union to have a cognitive and operational framework on energy planning and on how to accelerate the sustainability of urban systems.